Analisis Potensi Risiko Menggunakan Metode Hazard Identification, Risk Assessment, and Determining Control (HIRADC) pada Lapangan Penumpukan Petikemas Area LA 3 di PT. XYZ - Mahardika, Devin Isra; Sari, Rizqi Novita (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
Operational activities in container stacking yards involve significant occupational safety risks due to interactions between workers, heavy equipment, and operational vehicles. This study aims to identify hazards, assess risk levels, and determine risk control measures using the Hazard Identification, Risk Assessment, and Determining Control (HIRADC) method in the container stacking yard of Area LA 3 PT. XYZ. The study was conducted through field observations and interviews with the HSSE department. The results identified 15 hazards with varying risk levels, consisting of moderate, high, and very high risks, with the highest risk arising from manual twistlock operations. Risk controls focus on engineering and administrative measures supported by personal protective equipment. The HIRADC method is effective in reducing risks to acceptable levels.